Museum-Based History Learning Innovation With Outing Class Model - Amirullah; Patahuddin (Technium Social Sciences Journal, 2023)
The historical learning approach is strengthened by students seeking, discovering, observing and developing historical events as a dynamic science through a methodological approach, bringing objects closer, or student learning spaces in the learning process, so it is necessary to study with historical object approaches such as museums so that students are able to find creativity and their innovation is even wider. Strengthening Indonesian history learning materials, apart from teachers, teaching materials in the form of books, articles or modules with museum objects by developing the Outing Class model, where museums are the main attraction opening space and horizons for students’ thinking and creativity by not only showing historical objects which are displayed in museums, but are able to think critically, observe, study and find the origins of these historical sources. Museums as learning resources are able to increase understanding, study facts, concepts, principles, laws, theories and ideas, ideas and innovations at the memory level, students are able to apply them effectively in solving them so as to acquire creative and innovative historical thinking skills and foster historical awareness for students.